2015
DOI: 10.4028/www.scientific.net/amm.756.659
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cutting Forces in Oblique Cutting

Abstract: This study describes the method of determining cutting force components in oblique turning. The scheme of how the investigations were performed is presented. The characteristic curves of cutting force components vs. thickness of the material removed, tool clearance and tool rake angles are shown. The study presents the data, which have been obtained during the experimental investigations and analytically calculated, on how the cutting forces are subject to changes depending on a cutter angle, cutting depth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Mikolajczyk et al [18] uses the name "oblique turning" and presents new, original constructive solutions of special tools with continued edge and high value of cutting angle λs, for which patent protection was requested [19]. The name "oblique turning" is also used by Filippov [20]. To avoid ambiguities, it is expected that the name "tangential oblique turning" proposed by the authors of the present paper will be imposed.…”
Section: Particular Schemes Of Machining By Turningmentioning
confidence: 87%
“…Mikolajczyk et al [18] uses the name "oblique turning" and presents new, original constructive solutions of special tools with continued edge and high value of cutting angle λs, for which patent protection was requested [19]. The name "oblique turning" is also used by Filippov [20]. To avoid ambiguities, it is expected that the name "tangential oblique turning" proposed by the authors of the present paper will be imposed.…”
Section: Particular Schemes Of Machining By Turningmentioning
confidence: 87%
“…In early studies by Kobayashi and Thomsen [16] the friction on the worn flank of cutting tools has been experimentally studied. They found that plastic flow occurs in the work-piece beneath the tool flank.…”
Section: Oblique Cutting Analysismentioning
confidence: 99%
“…The planned experiment, unlike the unplanned one, provides the maximum amount of information and performs the task very efficiently, e.g., in obtaining constants and exponents in empirical exponential dependencies that create a mathematical model [44].…”
Section: Design Of the Composite Plan Of The Experimentsmentioning
confidence: 99%